The interstellar medium content of galaxies in the ALMA era. Issue Volume 15:Issue S352(2019) (June 2019) - Aravena, Manuel
Abstract: The advent of the Atacama Large Millimeter/submillimeter Array (ALMA) has enabled a new era for studies of the formation and assembly of distant galaxies. Cosmological deep field surveys with ALMA and other interferometers have flourished in the last few years covering wide ranges of galaxy properties and redshift, and allowing us to gain critical insights into the physical mechanisms behind the galaxy growth. Here, we present a brief review of recent studies that aim to characterize the interstellar medium properties of galaxies at high redshift ( z > 1), focusing on blank-field ALMA surveys of dust continuum and molecular line emission. In particular, we show recent results from the ALMA Spectroscopic Survey in the Hubble Ultra Deep Field (ASPECS) large program.